(untitled) (Research, Society and Development, 2019)
Scratch, SuperLogo and Learning Objects are tools that can help teachers in the classroom in a variety of levels of education, so these tools can stimulate the creativity and interest of those involved. This paper has two general objectives: to identify how Scratch and Logo softwares are being used to Mathematics teaching and which Learning Objects are being used to Mathematics teaching. The methodological approach used, it was steps adapted from a Literature Systematic Review, conducted in Brazilian journals in the Teaching area - 2013-2016 quadrennium, Qualis A1 and A2, for the Scratch and SuperLogo softwares and B2, for the Learning Objects. As considerations, we found in the stratum A1 and A2, 15.864 papers, of which only 4 dealt with the subject SuperLogo/Scratch, and only two actually dealt with the Mathematics teaching topic. Thus, the results indicate a small amount of work, 0.025% for Scratch and SuperLogo and 0.03% for Learning Objects, these underscores the need for more research related to the theme.